PERFORMANCE OF SOCIAL WORKERS AT CHILDREN'S REHABILITATION INSTITUTION REQUIRES SPECIAL PROTECTION IN PAGADEN SUBANG - Novia Norma Yunita; Aep Rusmana; Yudi Muryanto (Indonesian Journal of Social Work, 2020)
This research contains an overview of the results of research on the Performance of Social Workers at Children’s Social Rehabilitation Institution Requires Special Protection in Pagaden Subang. The objective of this research is to ascertain the performance social workers which include the aspects of work performance, discipline, creativity, collaboration, and responsibility. Researcher used a descriptive method with a qualitative approach. Informants in this research were determined using purposive sampling with a total of 8 informants consisting of structural officials, social workers, caregivers and foster children. Data collection technique was used in-depth interviews; observation and documentation study. The research results showed that social workers at the Children’s Social Rehabilitation Institution Requires Special Protection in Pagaden Subang have a good work performance,  disciplined,  creative, cooperation and coordinate with various parties, and of course responsible  in carrying out  tasks. However, social workers are not capable and serious in carrying out their duties. Based on this the researcher proposes the program "Capacity Building of Social Workers through Technical Guidance in Providing Services to Children" which aims to increase the awareness of social workers about the urgency in handling children problems, increase the motivation of social workers to improve their skills and sincerity in carrying out tasks, and develop techniques in providing services to children.